PENGARUH JALAN LINGKUNGAN SEBAGAI RUANG INTERAKSI SOSIAL TERHADAP LINGKUNGAN PERMUKIMAN BUNGUR, JAKARTA PUSAT - Nany Yuliastuti; Adinda Sekar Tanjung (Diponegoro University, 2011)
Streets are one of important network that will connect between area. Streets are the stage for commerce and exchange of goods, even for doing work, especially in eastern countries (Jacobs in Kiang et al, 2010:160). Street of Asia have been and continue to evolve as distinct from those of the west, reflecting the unique Asian cultures (Dayaratne in Kiang et al, 2010:63). The unique can be looked from street that used for held community festival, held funeral, street market, and social activity space, etc.Residential street became public space that very useful for social interaction space (visible in daily activity and community festival). Activities that happen on the street eventually will add other functions on the street as a space of social interaction. Residential streets in the Bungur Sub District, Central Jakarta used by the public as a space for exchanging ideas, buying and selling, children's playground, and an annual festival.The aim of this research is to analyze influence residential street and alley function as social interaction space on neighborhood environment. However, research method that used in this final project is quantitative with survey research strategy and statistic descriptive as analysis method. The results showed that the residential streets in Bungur Sub District has become a public space that allows people to interact with each other (shown by a variety of activities). Social interaction has strengthened the social ties and realized a strong kinship in these neighborhood.